2013
DOI: 10.1093/jnci/djt164
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Vascular-Endothelial Protein Tyrosine Phosphatase Inhibition on Breast Cancer Vasculature and Metastatic Progression

Abstract: Our results demonstrate that pharmacological VE-PTP inhibition can normalize the structure and function of tumor vessels through Tie-2 activation, which delays tumor growth, slows metastatic progression, and enhances response to concomitant cytotoxic treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
93
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(105 citation statements)
references
References 41 publications
6
93
1
Order By: Relevance
“…phorylates VE-cadherin, as we showed, but also couples with and dephosphorylates TIE2, a receptor for both angiopoietin 1 (ANG1) and ANG2, which regulate endothelial permeability and angiogenesis by antagonizing each other (25,30,35,36). In tumors, VE-PTP inhibition normalized the structure and function of tumor vessels through TIE2 activation (35). Since ANG2 contributed to the loss of endothelial barrier function in sepsis (37), it is possible that some of the barrierenhancing effects observed in our VE-PTP depletion studies may be due to activation of ANG2/TIE2 signaling.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…phorylates VE-cadherin, as we showed, but also couples with and dephosphorylates TIE2, a receptor for both angiopoietin 1 (ANG1) and ANG2, which regulate endothelial permeability and angiogenesis by antagonizing each other (25,30,35,36). In tumors, VE-PTP inhibition normalized the structure and function of tumor vessels through TIE2 activation (35). Since ANG2 contributed to the loss of endothelial barrier function in sepsis (37), it is possible that some of the barrierenhancing effects observed in our VE-PTP depletion studies may be due to activation of ANG2/TIE2 signaling.…”
Section: Discussionsupporting
confidence: 53%
“…Thus, HIF2α-dependent upregulation of VE-PTP expression resulting in dephosphorylation of VE-cadherin at Y658, Y685, and Y731 is consistent with the model (Figure 9) that the dephosphorylation switch is a key endogenous barrier-enhancing anti-inflammatory mechanism. phorylates VE-cadherin, as we showed, but also couples with and dephosphorylates TIE2, a receptor for both angiopoietin 1 (ANG1) and ANG2, which regulate endothelial permeability and angiogenesis by antagonizing each other (25,30,35,36). In tumors, VE-PTP inhibition normalized the structure and function of tumor vessels through TIE2 activation (35).…”
Section: Discussionmentioning
confidence: 53%
“…Recently, it was reported that suppressing VE-PTP with AKB-9778 suppresses micrometastases in a breast cancer model (56). The demonstration that AKB-9778 promotes maturation of AKB-9778 may have advantages over selective VEGF antagonists in the treatment of DME.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the zebrafish/tumour xenograft model represents a rapid and suitable test to screen small molecules with potential antitumor activity and using a small amount of compounds, whereas larger or non-water-soluble molecules can be injected into the body of the embryo to ensure drug uptake. The rapidity of this procedure makes this model very useful to perform preclinical drug screening, to test and validate new compounds that are able to significantly inhibit tumour-induced angiogenesis, invasiveness and metastatic dissemination, as already described in several tumours implanted in zebrafish embryos (Moshal et al 2011, Goel et al 2013, Chen et al 2015, Zheng et al 2016.…”
Section: Zebrafishmentioning
confidence: 99%